HECARE: SUSTAINABILITY START-UP INNOVATION BASED ON CIRCULAR ECONOMY THROUGH PROCESSING FOOD WASTE INTO PRODUCTS WITH HIGH USE VALUE - Purmayanti, Ni Putu; Suyantini, Kadek Enik; Ardani, Kadek Juli; Widyastuti, Dominica Arni; Hatta, Holila (Journal of Business And Entrepreneurship, 2023)
Indonesia become a country with the largest food waste producer in ASEAN in 2021 with the amount of waste reaching 20.9 tons per year and will increase every year has a significant impact on the environment. Food waste produces methane and carbon dioxide gas compounds which result in decreased oxygen levels in the earth's atmosphere. Therefore, it is necessary to have special handling of the problem of food waste so that it does not increase in the future. Handling this environmental problem is closely related to the implementation of the 13th SDGs goals related to tackling climate change. Develop startups that can answer these problems can be one of the solutions, in line with this, startup companies that are part of the digital economy contribute to the digital economy as part of the digital economy contributed 4% of GDP. Therefore, it is necessary to know how to plan for the development of circular economy-based startups, identify the influence and role of star-ups, and how to take steps to design strategies to build consumer brand awareness of the Start-Up developed. The subjects of this study were respondents who were taken by random sampling technique. Data collection was carried out using questionnaires, interviews, and documentation Afterwards, it was analyzed using qualitative methods by conducting credibility tests (time triangulation and member checks), transferability tests and dependability tests, and then the interview results were analyzed using qualitative descriptive methods. From the results of the research conducted, the results of HECARE Start-up planning based on a circular economy, the influence and role of HECARE in sustainable development plans, and strategies for building consumer brand awareness in supporting startup sustainability. Research on HECARE focuses on three problem formulations, consisting of how to plan in developing start-up, operating and production processes in creating products with high use value, and strategies to build consumer brand awareness in supporting a start-up that are developed. Based on this, the development of HECARE was designed which has a scope on product innovation from food waste. The development of this startup is in line with the 8th SDGs goal, namely the goal to encourage sustainable and inclusive economic growth, employment and decent work for all by being sustainably managed based on a circular economy that has not existed in previous studies.